2011
DOI: 10.1186/1756-6614-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric evaluation of intracellular IFN-γ and IL-4 levels in thyroid follicular cells from patients with autoimmune thyroid diseases

Abstract: BackgroundIn recent few years is underlined that altered balance of pro- and anti-inflammatory cytokines play an important role in the pathogenesis of AITD.The aim of this study was to estimate intracellular INF-γ and IL-4 levels in thyroid-infiltrating lymphocytes and thyrocytes isolated from thyroid tissues in 54 adolescent patients aged 8-21 years, with Graves' disease (GD; n = 18), Hashimoto's thyroiditis (HT; n = 18) and non-toxic multinodular goiter (NTMG; n = 18).MethodsFresh thyroid tissues were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
11
1
3
Order By: Relevance
“…6 The elevated expression of IL-4 has been previously reported among patients with HT, which may explain the increased expression of GATA 3 among these patients. 29 However, no significant difference was noted between HT patients and the control group in the current study regarding expression of the T-bet/GATA 3 ratio; this suggests that both Th1 and Th2 cell-related immune responses may contribute to the pathogenesis of HT. Qin et al demonstrated increased expression of Th1-related cytokines in both the thyroid gland and PBMCs of HT patients.…”
Section: Discussioncontrasting
confidence: 40%
“…6 The elevated expression of IL-4 has been previously reported among patients with HT, which may explain the increased expression of GATA 3 among these patients. 29 However, no significant difference was noted between HT patients and the control group in the current study regarding expression of the T-bet/GATA 3 ratio; this suggests that both Th1 and Th2 cell-related immune responses may contribute to the pathogenesis of HT. Qin et al demonstrated increased expression of Th1-related cytokines in both the thyroid gland and PBMCs of HT patients.…”
Section: Discussioncontrasting
confidence: 40%
“…Both immune cells and thyroid cells themselves secrete IFN-γ in HT, and it may be responsible for the continuation of the inflammatory process within the thyroid gland ( 18 , 19 ). So it could reasonably be proposed that IFNs are an important pathogenic factor in salivary gland hypofunction in HT.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenes activated in thyroid carcinomas, including RET/PTC, RAS and BRAF, which trigger the MAPK cascade, can induce a cell-autonomous proinflammatory transcriptional program in thyrocytes, which includes expression of cytokines, chemokines and their receptors (7). Proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interferon (IFN)-γ, are important inflammatory mediators of these processes (8,9). TNF-α and IFN-γ are pleiotropic cytokines expressed in various types of tumor cells and cells in the tumor microenvironment, exerting a variety of pro-tumoral activities in solid tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%